Network analysis: definition, origins, growth and future - Cárdenas, Julián (Pensando Psicología, 2016)
Network analysis or social network analysis is the solution to many problems of research. Network analysis is a theoretical and methodological approach stating that the most important thing is to study relationships, ties or contacts among actors1. Any type of relationship can be subject to network analysis: relations among individuals or organizations, communications, knowledge transfer, economic transfers and, even, neural connections.